Discussion on emergency response capability configuration for inherent safe HTR. (August 2018) - Ding, Hongchun; Tong, Jiejuan; Zhang, Liguo; Mao, Cui
Highlights: Inherent safety features for HTR are outlined. Emergency response capability and their provisions fit for HTR are discussed. Significantly simplified emergency requirement is expected for HTR. Abstract: The design philosophy in High-Temperature Gas-Cooled Reactor (HTR) ensures its inherent safety features, and these inherent safety features further determine its different accident characteristics. The severe core damage can be eliminated by adequate arrangements in HTR, and the fuel temperature will never go beyond the failure limitation to cause significant radioactive release. Therefore, the radioactive material released into the atmosphere even for the most severe anticipated accident of HTR is much smaller than that of Light Water Reactors (LWRs) with the same rating. In this sense, the emergency response capacities (ERCs) stipulated for LWRs are not necessarily all suitable for HTR. For example, the study on emergency planning zone (EPZ) for HTR shows that it could be limited within the exclusion area boundary, about several hundred meters away from the reactor, which is much smaller compared to that in LWRs. In this paper, the other prime ERCs besides EPZ will be re-evaluated one by one for HTR nuclear power plant (NPP) with such inherent safety features. The discussion in this paper is based on high temperature gas cooled reactor pebble-bed module (HTR-PM) being constructed at Shidao Bay, Shandong Province, China. It can be concluded that the offsite emergency planning for HTR could be largely replaced by the conventional industrial emergency system for non-nuclear industries; and some onsite ERCs, such as emergency facilities, emergency communication and notification, can be simplified in terms of radiation protection and urgency requirement respectively.